- Uji Efektivitas Ekstrak Etanol Kulit Jeruk Sunkist (Citrus sinensis (L.) Osbeck) Terhadap Kadar Gula Darah Tikus Wistar (Rattus norvegicus) dengan Hiperkolesterolemia yang di Induksi Streptozotocin. : UJI EFEKTIVITAS EKSTRAK ETANOL KULIT JERUK SUNKIST (Citrus sinensis (L.) Osbeck) TERHADAP KADAR GULA DARAH TIKUS WISTAR (Rattus norvegicus) DENGAN HIPERKOLESTEROLEMIA YANG DI INDUKSI STREPTOZOTOCIN - Depari, Sania Angelisa F; Rambe, Daffa Jihan Azmi; Meilando, Rifki; Lisya, Cut; Mutia, Maya Sari; Lubis, Yolanda Eliza Putri (Biospecies, 2021)
The Condition of high blood sugar levels in people with diabetets appears to trigger an increase in LDL and decrease HDL level where in people with diabetes the energy obtained by the body comes from the decomposition of fat and protein metabolism.â€Sunkist orange peel (Citrus sinensis (L.) Osbeck) is reported to have antidiabetic, anti-hypercholesterolemia, anti-inflammatory and antioxidant activities. This study aims to find out the effectiveness of Sunkist orange peel ethanol extract (Citrus sinensis (L.) Osbeck) on blood sugar levels at doses of 500, 750 and 1000 mg/kgBB. This study used the True Experimental Pre-Test and Post-Test Control Group as research design where sunkist orange peel was extracted by maceration method and was given orally for 14 days to streptozotocin induced wistar rat with hypercholesterolemia. Statistical test results showed that ethanol extract of Sunkist orange peel was able to lower blood sugar levels and cholesterol levels of h streptozotocin induced wistar rat with hypercholesterolemia (p<0.05). The most effective dose of Sunkist orange peel ethanol extract in lowering blood sugar levels and cholesterol levels of streptozotocin induced wistar rat with hypercholesterolemia is 1000mg/kgBB.